2021
DOI: 10.1002/oby.23299
|View full text |Cite
|
Sign up to set email alerts
|

Use of prescription medications associated with weight gain among US adults, 1999‐2018: A nationally representative survey

Abstract: Objective: This study aimed to evaluate trends in the use of obesogenic medications among adults.Methods: Cross-sectional data on adults aged ≥20 years are from the 1999 to 2018 National Health and Nutrition Examination Survey (n = 52,340). Obesogenic medications were defined according to the 2015 Endocrine Society guidelines on the pharmacological management of obesity. Weight status was categorized according to BMI.Trends in prior 30-day use were evaluated. Results:In NHANES 2017-2018, 20.3% of US adults use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
(37 reference statements)
0
17
0
Order By: Relevance
“… 10 In fact, data from the National Health and Nutrition Examination Survey (2017–2018) showed that 20% of US adults are on weight inducing medications. 154 …”
Section: Resultsmentioning
confidence: 99%
“… 10 In fact, data from the National Health and Nutrition Examination Survey (2017–2018) showed that 20% of US adults are on weight inducing medications. 154 …”
Section: Resultsmentioning
confidence: 99%
“…All medications were converted to a standard generic drug name. Obesogenic medications were identified from current Endocrine Society Clinical Practice Guidelines, further limited to those that has potential non-obesogenic alternatives, 11 , 12 , 22 and included certain anticonvulsants, antidepressants/antianxiety drugs, antipsychotics, beta-blockers, corticosteroids, and antidiabetic medications (see detailed obesogenic medication list and potential non-obesogenic alternatives in Supplemental Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A priori , we chose to evaluate comorbidities that were the most common indications for obesogenic medication use. 12 Hypertension, diabetes, cardiovascular disease (coronary heart disease, stroke, or heart failure), and arthritis were defined as a self-reported physician diagnosis of the conditions. The presence of depressive symptoms was defined as having five or more symptoms from the Patient Health Questionnaire, a nine-item instrument (PHQ-9) to screen depression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic, as upwards of 10% of U.S. adults take beta-blockers. 19 This is also relevant for states where HR and BP may uncouple to varying degrees (eg, sleep) or conditions of irregular HR (eg, atrial fibrillation, common among adults with hypertension).…”
Section: Limitations Applying Traditional Validation Approaches To Cu...mentioning
confidence: 99%